Defensor civitatis. Późnorzymski organ ochrony prawnej - Kania-Kaniowski, Piotr (Instytut Historyczny Uniwersytetu Wrocławskiego, 2023)
In the 4th century, an official with the title defensor civitatis became widespread in the Roman Empire. His task was to protect the poor from administrative injustices. Note worthy were his powers regarding taxation, which served the state’s fiscal goals by protecting sources of tax revenue. Initially, the defensor enjoyed a certain level of independence, but over time the position became subordinated to the local elites. In the 5th and 6th centuries, the original function of this official was distorted.
Keywords: defensor civitatis; organ ochrony prawnej; podatki; późne cesarstwo rzymskie